ANALISIS KESULITAN KEMAMPUAN MEMBACA PEMAHAMAN CERITA FIKSI PADA SISWA KELAS IV SDI BERTINGKATOEPURA 4 KOTA KUPANG - Arki Bansole; Roswita L Nahak; Yulsi M Nitte (STKIP Subang, 2026)
Bansole Arki 2025, Analysis of Difficulties in Reading Comprehension of Fiction Stories in Fourth Grade Students of SDI Bertingkat Oepura 4, Kupang City. Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University. Supervisor 1. Roswita L. Nahak, S.Pd.M. Pd; Supervisor 2. Yulsi Marselina Nitte, S.H., M. Pd. This study aims to describe the difficulties in reading comprehension of fiction stories in fourth grade students of SDI Bertingkat Oepura 4, Kupang City. The research method used is descriptive qualitative. This study aims to apply three elements in reading comprehension of fiction stories: the main types of difficulties faced in reading, factors that influence reading ability, and strategies applied to improve reading ability. Data collection techniques were carried out through interviews, observation, and documentation. The data collection instruments in this study were interview sheets, observation guidelines, and test sheets. The results of the study indicate that the reading comprehension ability of fourth-grade students in fictional stories is as follows: Students have difficulty understanding fictional stories due to limited vocabulary mastery, which makes it difficult for them to understand the meaning of words and phrases in the text, which hinders comprehensive comprehension of the story. Students often have difficulty understanding the structure of fictional stories, such as plot, moral, and narrative, so they cannot follow the story well. Students have difficulty identifying themes, so they have difficulty connecting events in the story with the main idea.